PENDUGAAN KETERDAPATAN AKIFER AIRTANAH DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI SUB-DAS CISATANG - KABUPATEN CIANJUR - Mardiana, Undang; Endyana, Cipta (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Geoelectric measurements committed in an attempt to obtain the presence, depth, thickness, number and spread of the aquifer. From the interpretation of Schlumberger geoelectric method (Sounding) acquired seven units of lithology, three units are classified as permeable layer, and four units as impermeable layers. The layer that functions as the aquifer has a resistivity value between 200-400 Ωm which is interpreted as a breccia with component-gravel gravel unit, 100-200 Ωm which is interpreted as breccia matrix supported by granule-sized components peble unit, and 50-100 Ωm which is interpreted as breccia matrix supported with gravel-sized component unit. Distribution of the three rocks in the study area is dominated by a nearly breccia grain supported. While units with resistivity values above 400 Ωm and under 50 Ωm interpeted as an impermeable layer-semipermeable. Faults that developed in the study area has direction a northwest-southeast. Those fault caused the fracture system that developed on volcanic deposits in this area. Therefore the zone bounded by two faults are thought to have better porosity values as the aquifer is supported by fracture with a higher intensity in surrounding area.